Decreased The Risk of Hyperbilirubinemia Incidence With The Initiation of Early Breastfeeding - Arief Yanto; Rochayati Rochayati; Edy Wuryanto (Media Keperawatan Indonesia, 2018)
Hyperbilirubinemia is a state where increase value of in serum bilirubin in the blood more > 5mg/dl, which is clinically characterized by jaundice on sclera and skin, hyperbilirubinemia can be caused by physiological processes, non-physiological, or a combination of both. Neonates were given early initiation will result in the expenditure of meconium early so tend to have a low risk of the occurrence of physiological hyperbilirubinemia. Research will aim to detect early initiation on the incidence of neonates physiologic hyperbilirubinemia in neonates born at Khadijah room Islamic Hospital Muhammadiyah Kendal. Research kind quasi-experiment by using plant form post test only in a body (one group post test only design). Population in this research patient newborn at Khadijah room Islamic Hospital Muhammadiyah Kendal. Research sample as much as 30  respondens early initiation and 30 respondens not early initiation by using technique purposive sampling. Data analysis included univariate analysis by finding frequency distribution, bivariate analysis with Mann-Whitney Test. The research result of bivariate analysis shows that neonates with early initiation total serum bilirubin value performed intervention group averaged 8,200mg/dl while control group averaged 11,647mg /dl. The initiation of early breastfeeding (IMD) effect on total serum billirubin content of the neonatus. The variables that have contributed to the total serum billirubin content were the implementation of early breastfeeding initiation (IMD) with an effect of 61.2% and influenced by other variables of 38.8%. The conclusion there is influence of early initiation of suckling on physiological hyprbilirubinemia at Islamic Hospital Muhammadiyah Kendal.